Case Report: Beating the assumed prognosis: homozygous familial hypercholesterolemia with unexpected long survival - Zlatohlávek, Lukáš; Becherová Beňová, Jana; Foglarová, Tereza; Dudková, Tereza; Hubáček, Jaroslav A. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFamilial hypercholesterolemia (FH) is a common autosomal codominant genetic disorder, with heterozygous FH (HeFH) affecting approximately 1 in 310 individuals. FH is characterized by elevated low-density lipoprotein cholesterol (LDL-C) levels, which are typically twice those of unaffected individuals, and by a markedly increased risk of premature atherosclerotic cardiovascular disease (ASCVD). Homozygous FH (HoFH) is rarer and presents substantial phenotypic variability, with total cholesterol levels ranging from 13 to 55 mmol/L.Case presentationsWe report three atypical cases of HoFH, with one patient being a homozygote for the c.1775G > A (p.Gly592Glu) variant and two patients being compound heterozygotes (c.340T > A/c.1775G > A, p.Phe114Ile/p.Gly592Glu and c.761A > C/c.910G > A, p.Gln254Pro/p.Asp304Tyr). All the patients presented with relatively mild clinical phenotypes, delayed diagnoses, and no evidence of early-onset ASCVD.ConclusionsThese cases underscore the clinical heterogeneity of HoFH and challenge the prevailing assumption that HoFH uniformly results in severe cardiovascular outcomes. Personalized treatment strategies are essential for improving prognoses and quality of life of affected individuals.